Single-/triple-stage biotrickling filter treating a H2S-rich biogas stream: Statistical analysis of the effect of empty bed retention time and liquid recirculation velocity. (2nd December 2019) - Salehi, Reza; Chaiprapat, Sumate
ABSTRACT: Biogas containing H2 S has limited use in electricity and heat production as H2 S can be corrosive to metal equipment. Bio-filtration has proved to be a suitable technology for biogas desulfurization because of economical and environmental benefits over physicochemical techniques. In the present study, a response surface methodology using 3 2 full factorial design was employed to determine the effects of two operating parameters, namely empty bed retention time (EBRT: 100–180 sec) and liquid recirculation velocity (LRV: 2.4–7.1 m 3 m −2 h −1 ) on H2 S removal efficiency (%) in single-stage and triple-stage bio-trickling filters (SBTF and TBTF) treating an H2 S-rich biogas. Quadratic model was found to be the best predictive model for H2 S removal efficiency. The results indicated that H2 S removal efficiency was significantly influenced by the synergistic effect of linear terms of EBRT and LRV with a greater effect associated with EBRT. However, the quadratic term of LRV had an antagonistic effect. The quadratic term of EBRT and cross-product term between EBRT and LRV did not exhibit a significant effect on H2 S removal efficiency. The predicted values from the established models showed a close agreement with the experimental data with the coefficient of determination (R 2 ) of 0.99 for H2 S removal efficiency in both SBTF and TBTF. Response analysis demonstrated that the performance of TBTF was superior compared to SBTF. Implications: Bio-trickling filter technology has gained a lot of attention for biogas desulfurization because it is economically and environmentally superior over chemical methods. Empty bed retention time (EBRT) and liquid recirculation velocity (LRV) are crucial variables influencing the performance of bio-trickling filters. In this work, the authors established a model that can properly predict H2 S removal efficiency in a single/triple bio-trickling filter (SBTF and TBTF) treating H2 S-rich biogas with regard to the individual and interaction effects between EBRT and LRV. Analysis with the help of response surface methodology indicated that TBTF was more efficient compared to SBTF for H2 S removal.